Qualidade da semente de soja tolerante ao glifosato, produzida em condições favoráveis - Silva, Fernanda Favoreto (2007)
This work has aimed to evaluate the quality of glyphosate-tolerant seeds of soybean genotypes of early, mid-, and late season, produced in adequate conditions. Experiments took place in two phases. Firstly, in a field one, with three variety competition trials; 6 glyphosate-tolerant genotypes of soybean were evaluated: early season (BR01-71210, BR02-64301, BRSMG 750SRR, BRS Favorita RR, BRS Valiosa RR e M-Soy 8008 RR); mid-season (BR02-71943, RRMG03-9511, RRMG03-9563, RRMG03-9565, M-Soy 8585 RR e CD 219 RR); and late season (BR01-66633, BRSMG 850GRR, BRSMG 811CRR, RRMG03-9184, BRS Silvânia RR e M-Soy 8787 RR). The second phase took place at the Universidade Federal de Uberlândia s laboratory of seed research. Visual quality, wetness degree, weight of one thousand seeds, germination, plantules vigor, electrical conductivity, tegument, and emergence in sand of seeds produced in the field trials were evaluated. Independent experiments for each season were designed in full randomized blocks of 6 x 2 factorial designs. The first factorial design corresponds to the genotypes; the second one, to cropping periods (physiological maturity, cropping point), with four replications. Results led to the following conclusion: a) early season genotypes MGBR 01-71210 and M-Soy 8008 RR produced seeds of superior quality in comparison with the rest; b) mid-season genotypes RRMG 03-9563 produced seeds of worst quality; c) late season M-Soy 8787 RR e RRMG 03-9184 produced seeds of better and worst quality respectively; d) no matter the season, the quality of seeds cropped during the physiological maturity surpassed seeds cropped during the cropping point.